Respuesta :

Zezima

Answer:

x = -43

y = -4

Step-by-step explanation:

In this question, you will have to find the value of x in terms of y using one of the equations and substituting the value in the other equation or vice versa.

Let's assume the numbers x and y, now we write the expressions.

x + y = -47

x - y = -39

Take the second equation and find x.

Calculations:

x - y = -39 (Add y on both sides)

x = -39 + y

Now that you got the value of x in terms of y, we can substitute.

Calculations:

(-39 + y ) + y = -47

2y - 39 = -47

2y = -8

y = -8/2 = -4

y = -4

Now that we got y, we can substitute that value in any of the equations to find x.

x - 4 = -47 or x + 4 = -39

x = -43

X = -43 Y=-4 is the answer I think?